Subthalamic nucleus stimulation attenuates motor seizures via modulating the nigral orexin pathway - Xue, Tao; Wang, Shu; Chen, Shujun; Wang, Huizhi; Liu, Chong; Shi, Lin; Bai, Yutong; Zhang, Chunkui; Han, Chunlei; Zhang, Jianguo (Frontiers in Neuroscience, 2023)
Background Focal motor seizures that originate in the motor region are a considerable challenge because of the high risk of permanent motor deficits after resection. Deep brain stimulation of the subthalamic nucleus (STN-DBS) is a potential treatment for motor epilepsy that may enhance the antiepileptic actions of the substantia nigra pars reticulata (SNr). Orexin and its receptors have a relationship with both STN-DBS and epilepsy. We aimed to investigate whether and how STN inputs to the SNr regulate seizures and the role of the orexin pathway in this process. Methods A penicillin-induced motor epileptic model in adult male C57BL/6 J mice was established to evaluate the efficacy of STN-DBS in modulating seizure activities. Optogenetic and chemogenetic approaches were employed to regulate STN-SNr circuits. Selective orexin receptor type 1 and 2 antagonists were used to inhibit the orexin pathway. Results First, we found that high-frequency ipsilateral or bilateral STN-DBS was effective in reducing seizure activity in the penicillin-induced motor epilepsy model. Second, inhibition of STN excitatory neurons and STN-SNr projections alleviates seizure activities, whereas their activation amplifies seizure activities. In addition, activation of the STN-SNr circuits also reversed the protective effect of STN-DBS on motor epilepsy. Finally, we observed that STN-DBS reduced the elevated expression of orexin and its receptors in the SNr during seizures and that using a combination of selective orexin receptor antagonists also reduced seizure activity. Conclusion STN-DBS helps reduce motor seizure activity by inhibiting the STN-SNr circuit. Additionally, orexin receptor antagonists show potential in suppressing motor seizure activity and may be a promising therapeutic option in the future.